Social support sources for people with palliative care needs at home: a scoping review - Trudy Schutter; Ian Koper; Kris Vissers; Jeroen Hasselaar (BMC Palliative Care)
Abstract Background Recent literature suggests an increase in attention for the social dimension of palliative care. However, who provides social support to patients with palliative care needs at home and their relatives is often unclear, and insight in the role of the community and professionals with a main focus on social support, not being health care professionals, is lacking in this respect. Therefore, in this study we explore social support for people with palliative care needs residing at home and their relatives, provided by the community and professionals from the welfare domain, and want to understand when social support is experienced as sufficient by the recipient. Methods A scoping review was conducted to search for literature on social support by the community and professionals from the welfare domain to people with palliative care needs at home, using the databases PubMed and Web of Sciences for studies published between January 1, 2007, and June 1, 2023. Results Social support to people at home with palliative care needs and their relatives is mainly provided by informal caregivers, namely family, friends and neighbours. These people providing social support is perceived as normal, natural and is expected by the recipient. Social support by the wider community and by professionals from the welfare domain can enhance, complement and/or substitute this support. Within the 27 included articles, nine studies provide results of social support interventions, which show that volunteer or professional services aimed at enhancing and mobilizing the informal social network of the patient are an important way of building supportive and sustainable social support networks. Conclusions Community sources and professionals with a main focus on social support such as social workers can enhance, complement and substitute social support provided by the informal network, if needed. Structured approaches can improve recognition of unmet social problems and needs of people with palliative care needs at home.